Determinação da idade dental de crianças brasileiras nordestinas: novos valores de conversão de maturidade dental para população específica - Maia, Maria Cristina Germano (2010)
Since Demirjian's system of estimating dental maturity was first described, many researchers from different countries have tested its accuracy among diverse populations. Some of these studies have pointed out a need to determine population-specific standards. In Brazil, the Northeast region is the one that most suffers the negative impact of exodus, specially related to the increase of abandoned children in the cities. The aim of this study was to test the accuracy of Demirjian's system for assessing the dental maturity of northeastern Brazilian children, so as to present a scale for maturity score conversion into dental age developed specifically for this population. This could be used for forensic, anthropological and legal matters, and also as a model for other countries attempting to formulate their own conversion scales. Panoramic radiographs of 1,491 children (821 females and 670 males), aged 7 to 13 years, from Ceará state, northeast Brazil, were assessed by a single observer to determine dental age (DA) according to Demirjian's system. The mean percentage of intra-observer agreement was 86.6%, with a mean Cohen's Kappa coefficient of 0.67 (substantial agreement). The DA was compared by paired t-test to subjects' chronological age (CA). The differences between CA and DA in all age groups were statistically significant (p<0.0001), demonstrating a great advancement in DA among Brazilians. Scatter plots were drawn for both genders, and the data were fitted to a growth curve, y = 100/ (1 + e-a(x b)). Graphs corresponding to the 50th percentile curves were produced. A table with new values for the conversion of maturity score into dental age for northeastern Brazilian children is presented. The great advancement in DA, as obtained by Demirjian's system in this population, justified the determination of specific scores for dental maturity assessment